Sensitivity analysis in psychological and medical research [data] - Dönnhoff, Ivo; Bergner, Thilo; Riedel, Caroline; Friederich, Hans-Christoph; Bugaj, Till Johannes (Universität, 2025)
This dataset contains all data and R code necessary to follow the tutorial "Sensitivity analysis in psychological and medical research: A tutorial using multiple imputation in a longitudinal case study". People interested in learning sensitivity analysis with multiple imputation are free to download the data and R code and follow along.
Gesehen am 18.08.2025
Keywords: Forschungsdaten; Datenbank